2003
DOI: 10.1159/000067129
|View full text |Cite
|
Sign up to set email alerts
|

Two-Peak Temporal Distribution of Stroke Onset in Greek Patients

Abstract: A circadian distribution with a single peak of stroke onset in the morning hours has been described in various countries. Analysis of the temporal pattern of symptom onset in a series of 1,253 Greek first-ever stroke patients revealed a circadian distribution with two incidence peaks between 08.00 and 10.00 h, and between 16.00 and 18.00 h. Considering the different etiopathogenic types of stroke, the same two-peak time pattern was evaluated in all stroke subgroups with the only exception of lacunar stroke, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
1
3

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 26 publications
2
24
1
3
Order By: Relevance
“…The two-peak temporal deterioration of vascular function observed in this study grossly coincides with the observed morning and evening increased incidence of cardiovascular events. [1][2][3][4][5] Thus, variation of arterial stiffening and endothelial function may have implications for our understanding of the diurnal peaks in cardiac and vascular events. However, it should be underscored that second peaking of vascular dysfunction due to arterial stiffening may not be robustly substantiated as it most probably depends on temporal peaking of BP, which is not always observed in the evening.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The two-peak temporal deterioration of vascular function observed in this study grossly coincides with the observed morning and evening increased incidence of cardiovascular events. [1][2][3][4][5] Thus, variation of arterial stiffening and endothelial function may have implications for our understanding of the diurnal peaks in cardiac and vascular events. However, it should be underscored that second peaking of vascular dysfunction due to arterial stiffening may not be robustly substantiated as it most probably depends on temporal peaking of BP, which is not always observed in the evening.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiovascular events such as stroke, sudden death and acute myocardial infarction have an increased incidence in the morning [1][2][3][4][5] and a smaller peak in the evening. The mechanisms involved in this variation in cardiovascular events are not clear, and may involve various factors such as augmented sympathetic activation, 6,7 haemodynamic changes, 8 neurohumoral factors and increases in coagulation.…”
Section: Introductionmentioning
confidence: 99%
“…Details and diagnostic categories of this study have previously been published [23]. All patients were examined by an internist and a neurologist within the first 48 h. In the same period, a noncontrast CT scan of the brain was also performed.…”
Section: Methodsmentioning
confidence: 99%
“…Since cardioembolic (CE) stroke is identified as the most frequent stroke subtype and AF seems to be the most important stroke risk factor in Greece [21,22], we investigated the circadian and seasonal variation in stroke incidence in patients with CE stroke due to AF, willing to examine if the recently described 2-peak diurnal variation of stroke onset in overall stroke patients in Greece [23] also appears among stroke patients of the above-defined target group.…”
Section: Introductionmentioning
confidence: 99%
“…Drugi maksimum broja obolelih se u nekim studijama prepoznaje tokom popodneva i rane večeri (86)(87)(88)(89).…”
Section: Dnevne Varijacije (Cirkadijalni Ritmovi) Obolevanja Od Muunclassified